Actinotalea soli sp. nov., isolated from Kubuqi Desert soil. Issue 12 (20th December 2022) - Du, Jie; Ping, Weiwei; Chen, Ya; Pang, Huancheng; Bai, Pengze; Cui, Siqi; Zhang, Jianli
Abstract : A Gram-stain positive, facultatively anaerobic, motile rod-shaped strain, BY-33 T, was isolated from a soil sample obtained from the Kubuqi Desert, PR China. Phylogenetic analysis based on 16S rRNA gene sequence similarity revealed that strain BY-33 T was most closely related to the genus Actinotalea, including Actinotalea ferrariae CF5-4 T (98.2 % similarity), ' Actinotalea subterranea ' HO-Ch2 T (98.0 %), Actinotalea solisilvae THG-T121 T (97.6 %), ' Actinotalea bogoriensis ' 69B4 T (97.5 %), Actinotalea fermentans M T (97.3 %) and ' Actinotalea carbonis ' T26 T (97.0 %). The strain grew at 0‒37 °C (optimum, 28–30 °C) and pH 6.0–11.0 (optimum, pH 9.0–10.0) and with 0‒8.0 % (w/v) NaCl (optimum, 3.0%) on tryptic soy agar. It had catalase activity, but no oxidase activity. The polar lipids of strain BY-33 T contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, and phosphatidylinositol mannosides. The major respiratory quinone of strain BY-33 T was MK-10 (H4 ). Its major fatty acids were anteiso-C15 : 0, anteiso-C15 : 1 A and C16 : 0 . The genomic DNA G+C content of strain BY-33 T was 73.0 mol% based on total genome calculations. The average nucleotide identity scores between the genomic sequences of strain BY-33 T and the other species of the genus Actinotalea were found to be low (ANIm <85.0 %, ANIb <77.0 % and OrthoANIu <78.0 %). Furthermore, the digital DNA–DNA hybridization and average amino acid identity values between strain BY-33 T and the closely related species ranged from 20.5 to 21.0% and from 62.2 to 72.2 %, respectively. Based on the results of phylogenetic, phenotypic, genotypic and chemotaxonomic analyses, it is concluded that strain BY-33 T represents a novel species within the genus Actinotalea, for which the name Actinotalea soli sp. nov. is proposed. The type strain is BY-33 T (=CGMCC 1.17460 T =KCTC 49362 T ).